Fear and anguish: the patient's experience in the intensive care unit - Keydis Sulay Ruidiaz-Gómez; Shirley Fernández-Aragón (Universidad Francisco de Paula Santander, 2020)
Objective: To understand the experiences of patients who have graduated from the intensive care unit of a tertiary care clinical institution in the City of Cartagena using Rosemarie Rizzo Parse's theory of human development as an approach. Materials and Methods: Phenomenological-interpretive study with a hermeneutic perspective, 11 adults graduated from the intensive care unit participated, the in-depth interview technique was used with a duration of 30 and 40 minutes, the data were analyzed through the technique of intentionality, reduction and constitution. Results: The study participants were eight adult men and three women, their experience was described with feelings of fear and anguish that included the subtopics: Good treatment; Imagination of death: My life, work and family; Feelings of loneliness; Spiritual strength and life changes. Conclusion: Being hospitalized in the intensive care unit managed to trigger an experience described as "fear and anguish", for the participants the family nucleus, spiritual strength, transformation and life changes are essential.